1993
DOI: 10.3346/jkms.1993.8.4.271
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on aberrations of chromosome 17 and proliferating cell fraction in lung cancer

Abstract: To better understand the relationship between specific chromosome changes found in human lung tumors and their phenotypic consequences a the tissue level, an in situ hybridization (ISH) procedure of chromosome 17 and immunohistochemistry of proliferating cell nuclear antigen (PCNA) were done. The deparaffinized sections were stained with pericentromeric probes for chromosome 17 and an immunohistochemical study of a monoclonal antibody against PCNA were performed. The numbers of chromosome signals were than com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The cells of the flaked lupine, meanwhile, exhibited different sizes of air vents (Figure 1c). These observations indicated that starch and protein were embedded and exhibited a rigid structure in the ground matrix (Lee and Kim, 1985). When lupine was heattreated by expansion and flaked, the cell wall was destroyed and the protein mass was enlarged, few starch granules were present in the network structure due to gelatinization at such a temperature.…”
Section: Lupine Seed Properties As Affected By Processing Methodsmentioning
confidence: 96%
“…The cells of the flaked lupine, meanwhile, exhibited different sizes of air vents (Figure 1c). These observations indicated that starch and protein were embedded and exhibited a rigid structure in the ground matrix (Lee and Kim, 1985). When lupine was heattreated by expansion and flaked, the cell wall was destroyed and the protein mass was enlarged, few starch granules were present in the network structure due to gelatinization at such a temperature.…”
Section: Lupine Seed Properties As Affected By Processing Methodsmentioning
confidence: 96%